Influence of Fiber Orientation on the Shear Properties of Steel Fiber-Reinforced Reactive Powder Concrete Beams - Kejia Yang; Kunliang Li; Yiwei Lin (Advances in Civil Engineering)
Steel fiber-reinforced reactive powder concrete (SFRPC) has good mechanical properties and is thus useful for engineering applications. Generally, the fibers in SFRPC are randomly distributed. To study the effects of the amount, length, and orientation of steel fibers on the shear strength of SFRPC beams, nonreinforced aligned steel fiber-reinforced reactive powder concrete (ASFRPC) beams were prepared using a large-scale electromagnetic field orientation device. Shear tests of specimens with a shear span ratio of 1.5 were performed under two fiber contents (1.0% and 2.0%) and three fiber lengths (20, 30, and 40 mm). The full-field strain during the loading process was obtained via the digital image correlation method, and the effects of fiber quantity and orientation on the shear strength of the beams were analyzed. The ASFRPC beams exhibited higher ductility but lower shear capacity than the SFRPC beams under the same conditions. The shear capacity increased with the quantity of steel fibers. According to the test results, the calculation formulas of the shear-bearing capacities of ASFRPC and SFRPC beams were established.